“Монгол, Хятадын харилцаанд Өвөр Монголын үүрэг, холбогдол” сэдэвт эрдэм шинжилгээний хурал болов (Journal of International Studies, 2004)
English title: The scientific conference on “The role and reliance of Inner Mongolia in Mongolian - Chinese relationships”